Valuing the Impact of Air Pollution in Urban Residence Using Hedonic Pricing and Geospatial Analysis, Evidence From Quito, Ecuador - Sebastian Borja-Urbano (SAGE Publishing, 2021)
Air pollution is one of the hazardous effects of urbanization. Hereby, one the most polluted cities in Ecuador is the Metropolitan District of Quito (DMQ). This study attempts to determine the marginal willingness to pay for a cleaner air in the DMQ using the impact of air pollutants on price properties. Spatial interpolation techniques visualized pollutant concentrations in the DMQ. Additionally, a hedonic price model estimated air pollution impact on properties. Results demonstrated hazard levels for at least three pollutants, being Particulate Matter PM 2.5 , Nitrogen Dioxide NO 2 , and Sulfur Dioxide SO 2 . Subsequently, the economic impact on the house market was statistically significant with a decrease in property value between 1.1% and 2.8%. These drop of value between 1,846.20 up to 4,984.74 US$ (United States Dollars) represents a substantial loss in property value for the DMQ and loss of revenues for the city.